Export Diversification, Externalities and Growth: Evidence for Chile - Dierk Herzer; Felicitas Nowak-Lehmann D. (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
It is frequently suggested that export diversification contributes to an acceleration of growth in developing countries. Horizontal export diversification into completely new export sectors may generate positive externalities on the rest of the economy as export oriented sectors gain from dynamic learning activities due to contacts to foreign purchasers and exposure to international competition. Vertical diversification out of primary into manufactured exports is also associated with growth since primary export sectors frequently do not exhibit strong spillovers. Thus, it is to be expected that both horizontal and vertical export diversification are positively correlated with economic growth. However, there have been remarkably few empirical investigations into the link between export diversification and growth. This paper attempts to examine the hypothesis that export diversification is linked to economic growth via externalities of learning-by-doing and learning-by-exporting fostered by competition in world markets. The diversification-led growth hypothesis is tested by estimating an augmented Cobb-Douglas production function on the basis of annual time series data from Chile. Based on the theory of cointegration three types of statistical methodologies are used: the Johansen trace-test, a multivariate error-correction model and the dynamic OLS procedure. The estimation results suggest that export diversification plays an important role in economic growth.
Keywords: 330